Keefektifan Media Pembelajaran Geogebra Dalam Memecahkan Persoalan Matematika - Mulyadi Mulyadi; Risky Marchel Tanjung; Azira Wina Kusuma; Fadya Levia Azahra; Tiara Sekar Maharani; Dilah Nur Fadilah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The purpose of this research is to analyze the effectiveness of Geogebra learning media in solving math problems among students. The method used in this study is the literature review method with a qualitative approach, which involves a literature review of library sources such as books, articles, journals. Data collection techniques were carried out by conducting literature studies and distributing questionnaires and test questions given to 10 students from class 4C in the 4th semester of Mathematics Education at Indraprasta University PGRI, who were considered to represent the entire research subject. The data analysis technique uses descriptive analytic by collecting data then compiling, analyzing and drawing conclusions. The results of this study indicate that Geogebra is less effective in solving mathematical problems due to lack of knowledge about Geogebra and low interest in using Geogebra.